High-Voltage Electrically Head Injury Presenting underlying Calvarial Osteomyelitis: Single Indonesian Tertiary Hospital Experience - Farid Yudoyono; Agung Budi Sutiono; M Zafrullah Arifin (Journal of Surgery and Surgical Research - Peertechz Publications, 2016)
Objective: To demonstrate the characteristic of high-voltage electrically head injury patients presenting underlying calvarial osteomyelitis. Methods: Retrospectively report of patients high-voltage electrically head injured with calvarial osteomyelitis from January 1st 2011 to December 31st 2013. The demographic variable namely age, sex, place of accident, present of calvarial osteomyelitis, Glasgow coma scale, surgical treatment type, grading of burn injury and total body surface area of burn (TBSA). Results: Eleven high-voltage electrically injured patients presenting with calvarial osteomyelitis, who admitted to the Emergency Unit Department of Neurosurgery Hasan Sadikin Hospital, All patients were males (100%). Their ages ranged between 24 and 51 years (average 23,7 years old) All patient (100%) suffered from calvarial osteomyelitis. Eight patient (77,7%) were high building worker at the time of incident, two patients were electric installation worker (18,18%). Entry point of electric wave 11 patients (100%) from head and outlet 11 patients (100%) from leg. Conclusion: Bone debridement in calvarial osteomyelitis is a difficult to treat infectious disease with a high relapse risk, cure is possible with appropriate treatment choices. Antibiotic treatment will provide more benefit if it is combined with appropriate and timely surgical treatment for both scalp and calvarial.